Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Cocopeat di Desa Andoolo Utama - Weka Gusmiarty Abdullah; La Ode Santiaji Bande; Indriyani Nur; Muhaimin Hamzah; Putu Arimbawa; Rizal Adi Saputra; Wa Ode Yatni Yansari; Fazilah, Nurul; Hidjriani (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Training and assistance in making coco peat was carried out by the service team in the main village of Andoolo to increase the community's knowledge and skills. This activity aims to ensure that residents can utilize coconut dregs effectively and sustainably through Input, Production Process, Output and Evaluation methods. Participants are trained in the process of making coco peat which is expected to increase income and support organic farming. The evaluation results show an increase in public understanding and interest in the use of coco peat and plans for its implementation on a wider scale.